Investigating Pre-Service Teacher’s Self-Confidence in Teaching Practicum Activities at Junior High School Level: A Case Study - Kusrin; Fitri, Annisa Ryani (IKIP Siliwangi, 2025)
Teaching practicum is considered very complicated task for many EFL pre-service teachers for they have to prepare perfect lesson plans, master the teaching materials, teaching method, teaching mental, and also student assessment. This present study through case study design, is focused on investigating pre-service teacher’s self-confidence during in their teaching practice. Two pre-service teachers of Educational English Department in Indonesia were recruited voluntarily. They were assigned to practice teaching English lesson in secondary school for one semester. Videos of their performance were taken during the class and interview and reflective journal were taken for the data source. Observation showed differences in self-confidence between the two participants. Participants with high self-confidence started the class with a positive attitude, built initial interactions, and used L2 flexibly, creating an interactive learning atmosphere. In contrast, participants with low self-confidence faced high anxiety, which affected their ability to teach and interact with students. In return to these results, this study may contribute benefits to pre-service English teachers, lectures, and English study program administer.